A semi-empirical estimation of ground and excited state dipole moments of zinc phthalocyanine from solvatochromic shift data - Ogunsipe, Abimbola (International Journal of Advanced Chemistry, 2018)
A semi-empirical determination of ground and excited state dipole moments of zinc phthalocyanine (ZnPc) from solvatochromic shifts is hereby presented. The ratio of the excited- and ground-state dipole moments of ZnPc ( ) was estimated by a combination of the Bakshiev and the Kawski-Chamma-Viallet’s equations, while the difference in the excited- and ground-state dipole moments (Dm) was estimated usingthe molecular-microscopic solvent polarity parameters ( ), alongside the Stokes’ shifts (Dῡ) in the various solvents. The dipole moment of ZnPc is significantly higher in the excited singlet state (me = 3.12 D) than in the ground state (mg = 1.50 D). Obviously charge separation is greater in the excited state of ZnPc than in its ground state.